The improvement of aluminium casting process control by application of the new CRIMSON process - Dai, Xiaojun J.; Jolly, Mark R.; Zeng, Binxu (Cranfield University, 2012)
All The traditional foundry usually not only uses batch melting where the aluminium alloys are melted and held in a furnace for long time, but also uses the gravity filling method in both Sand Casting Process (SCP) and Investment Casting Process (ICP). In the gravity filling operation, the turbulent behaviour of the liquid metal causes substantial entrainment of the surface oxide films which are subsequently trapped into the liquid and generate micro cracks and casting defects. In this paper a new CRIMSON process is introduced which features instead of gravity filling method, using the single shot up-casting method to realize the rapid melting and rapid filling mould operations which reduce the contact time between the melt and environment thus reducing the possibility of defect generation. Another advantage of the new process is the drastic reduction of energy consumption due to shortened melting and filling time. Two types of casting samples from SCP and ICP were compared with the new process. The commercial software was used to simulate the filling and solidification processes of the casting samples. The results show that the new process has a more improved behaviour during filling a mould and solidification than the two conventional casting processes.
Keywords: casting, aluminium, energy reduction